Understanding Dyspepsia - Marques, Susana Castro (2002)
Introduction: Dyspepsia can be defined as persistent or recurrent pain or discomfort in the upper abdominal quadrants, which may or may not be related to meals. Objectives: To conduct an updated and systematic review on dyspepsia, with a special emphasis on functional dyspepsia and on the family medicine setting. Methods: Literature review of relevant manuals and periodicals from the field, and a Medline search including articles published since 1995. Results overview: Definitions of dyspepsia and functional dyspepsia, their epidemiological framework and their more relevant aetiological and pathophysiological aspects are discussed. A diagnostic and therapeutic approach for dyspepsia is suggested, and the role of the family physician in following up these patients is highlighted. Finally, referral criteria for secondary care services are enunciated, and prognostic implications discussed. Conclusions: Dyspepsia is a common health problem in family practice accounting for 2 to 5% of all general/ family practice visits. Constant updating on pathophysiological mechanisms and diagnostic and therapeutic developments is therefore absolutely necessary.